Bibliometric insight into neoadjuvant immunotherapy in non-small cell lung cancer: trends, collaborations, and future avenues - Xu, Pengliang; Yu, Huanming; Bian, Hupo; Jia, Dan; Li, Wenhui; Dong, Hongfeng; Peng, Xiuhua (Frontiers in Immunology, 2025)
BackgroundNeoadjuvant immunotherapy (NIT) is a rapidly emerging paradigm for advanced resectable non-small cell lung cancer (NSCLC). However, there is no bibliometric analysis in this research field.ObjectiveTo analyze the hotspots and trends in the research of NIT for NSCLC and provide a reference for the study of NIT for lung cancer in China.MethodsRetrieve literature related to NIT for NSCLC from Web of Science, PubMed, and Scopus databases up to September 10, 2024. Use CiteSpace and VOSviewer software visualization software to analyze the keywords of country, author, institution, and literature.ResultsThere were 1575 references, and the overall annual publication volume showed an upward trend; Forde and Patrick M have published the most articles in the literature. The research hotspots mainly focus on chemotherapy, NIT for NSCLC, immunotherapy, neoadjuvant chemotherapy, pathological reactions, etc.ConclusionsThis is the first bibliometric study comprehensively summarizing NIT’s research trends and development in NSCLC. Our bibliometric assessment provides a panoramic view of the research milieu surrounding NIT for NSCLC, encapsulating the present state, evolving trends, and potential future directions, particularly emphasizing the promise of immunochemotherapy.